Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
The equation k = √3abc + a² - b² + c² - 5b is an algebraic expression
The value of k = √3abc + a² - b² + c² - 5b when a = -2, b = -2 and c = 3 is 25
How to solve the expression?
The equation of k is given as:
k = √3abc + a² - b² + c² - 5b
Where
a = -2, b = -2 and c = 3
Substitute a = -2, b = -2 and c = 3 in the equation of k
k = √(3 * -2 * -2 * 3) + (-2)² - (-2)² + 3² - 5*-2
Evaluate the root expression
k = 6 + (-2)² - (-2)² + 3² - 5*-2
Evaluate the exponents and the products
k = 6 + 4 - 4 + 9 + 10
Evaluate the sum and the difference
k = 25
Hence, the value of k = √3abc + a² - b² + c² - 5b when a = -2, b = -2 and c = 3 is 25
Read more about algebraic expressions at:
https://brainly.com/question/4344214
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.